A systematic review of the 5e model and problem-based learning for critical and collaboration skills - Nurhadi Nurhadi; Widodo; Merry Lapasau (Jurnal Konseling dan Pendidikan, 2025)
This systematic literature review examines empirical research on the integration of the 5E Instructional Model and Problem-Based Learning (PBL) in relation to students’ critical thinking and collaboration skills. Using an analytical thematic synthesis approach, 21 peer-reviewed empirical studies published between 2014 and 2025 were systematically selected and analyzed following PRISMA guidelines. The review identifies recurring patterns of pedagogical alignment between inquiry-based learning phases and problem-solving processes, as well as variations in reported learning outcomes across methodological designs. The findings indicate that integrated 5E-PBL implementations are consistently associated with positive trends in critical thinking and collaboration; however, the strength of evidence varies considerably depending on research design, measurement instruments, and contextual factors. Quantitative studies generally report statistically significant but moderate effects, while qualitative studies emphasize process-oriented learning gains. Importantly, the synthesis avoids causal claims and instead highlights associative instructional tendencies. This review provides the first structured mapping of pedagogical alignment between the 5E inquiry cycle and PBL stages to support higher-order and collaboration skills, offering a clarified conceptual foundation for future theory development and empirical investigation.